Indications for, and outcomes of, end ileostomy revision procedures. (4th December 2020) - Gilshtein, Hayim; Ghuman, Amandeep; Dawoud, Mirelle; Yellinek, Shlomo; Kent, Ilan; Sharp, Stephen P.; Wexner, Steven D.
Abstract: Aim: Ileostomy complications have been reported in >70% of cases. Older studies have shown ileostomy revision to be required in 23%–38% of patients over a 5–10 year period. There is a paucity of recent data addressing ileostomy revision surgery. We aimed to review end ileostomy revisions in a tertiary centre and analyse indications, procedures performed, outcomes and risks for such surgery. Methods: This was a retrospective review in a single institution colorectal referral practice. All patients aged >17 years who underwent a revision of an ileostomy at our institution from 2008 to 2019 were included. Indication for ileostomy revision, operative technique (parastomal vs. intra‐abdominal) and outcomes including length of stay, readmission rates, wound complications, medical complications and rate of stoma re‐revision were assessed. Results: Fifty‐three patients who underwent 72 end ileostomy revision procedures were included; 20 (27.8%) were re‐revision procedures. The majority (76.4%) had their original ileostomy created for inflammatory bowel disease. Indications for ileostomy revision were stoma retraction (36.1%), prolapse (22.2%), stenosis (18.1%) and parastomal hernia (29.2%). Of stoma revisions, 55.6% were performed by a parastomal approach vs. 44.4% by an intra‐abdominal approach. Procedures were a combination of laparotomy, laparoscopy or both. The average length of stay was statistically significantly lower in the parastomal approach revision group (2.3 days) compared to the intra‐abdominal approach revision group (10.3 days) ( P < 0.001). Readmission and wound complication rates were 6.9% and 15.3%, respectively, in the intra‐abdominal approach group alone. Medical complication rates were 20.8%. Conclusions: End ileostomy complications are common and surgical treatment may result in significant morbidity, readmission and reoperation. Patients should be counselled about these possibilities.